Analisis Efisiensi Pemasaran Bawang Daun di Desa Linonggasai Kecamatan Wonggeduku Barat Kabupaten Konawe - Ramlah Ramlah; Idrus Salam; Milawati Saranani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study aims to identify the marketing channels of spring onions and analyze the efficiency of spring onion marketing in the research area. The population in this study were all farmers in Linonggasai Village, Wonggeduku Barat District, Konawe Regency who grow spring onions and marketing institutions, namely 10 farmers, 4 collectors and 5 retailers, farmer samples were taken by census and trader samples used the snowball sampling method. Based on the results of field research, it can be concluded that; the marketing channels for spring onions in this research area are farmers to collectors to retailers and then to consumers. The margin obtained by collectors is IDR 10,000 / kg with a profit of IDR 8,500 / kg. While the margin obtained by retailers is IDR 10,000 / kg with a profit of IDR 8,900 / kg. The efficiency value of the spring onion marketing channel in the research area is efficient with a marketing efficiency level obtained by collectors of 2.5% and retailers of 1.5%, and the farmer share received by farmers is 72%.